A new approach to the analysis of multiple injuries using data from a national trauma registry - Aharonson-Daniel, L (BMJ Group, 2003)
Objective: To present a new systematic approach for summarizing multiple injury diagnosis data into patient injury profiles. Design: International Classification of Diseases, ninth revision, clinical modification injury diagnosis codes were classified using a modification of the Barell body region by nature of injury diagnosis matrix, then grouped by body region, injury nature, or a combination of both. Profiles were built which describe patients' injury combinations based on matrix units, enabling the analysis of patients, and not only the study of injuries. Setting: The Israeli national trauma registry was used to retrieve patient demographic data, injury details, and information on treatment and outcome. Patients or subjects: All hospitalized patients injured in road traffic accidents and included in the trauma registry from January 1997 to December 2000 were included. Main outcome measures: Patient profiles consisting of body regions, injury natures, their combination, and their clinical outcomes. Results: The study population comprised 17 459 patients. Head and neck injuries were the most frequent in all subpopulations except for motorcyclists who sustained most injuries in the extremities. Fractures were the most common injury nature (60%). Pedestrians and drivers had the highest proportion of multiple injuries in both profiles. Forty eight percent of the patients had a single cell profile. The most frequent conditions as a sole condition were extremity fractures (14%), internal injuries to the head (11%), and injuries of other nature to the torso (6%). Mortality, length of stay, and intensive care unit treatment varied dramatically between profiles and increased for multiple injury profiles. Inpatient death was an outcome for 3.3% overall; however, in patients with an internal injury to the head and torso, inpatient death rate was nine times higher, at 31%. Conclusions: Profiles maintain information on body region and nature of injury. The use of injury profiles in describing the injured improves the understanding of casemix and can be useful for efficient staffing in multidisciplinary trauma teams and for various comparisons.